REFUSAL OF THE POLISH CONSTITUTIONAL TRIBUNALTO APPLY THE ACT STIPULATINGTHE CONSTITUTIONAL REVIEW PROCEDURE - Radziewicz, Piotr (Review of European and Comparative Law, 2017)
One of the politically momentous and legally precedential constitutional problems of recent years which had to be faced by the Polish constitutional court has been the dispute whether it is possible to exclude the applicable statute defining the organization and procedure of the CT proceedings as a basis for adjudication.An analysis of the judgment of the Tribunal addressing that issue proves that the Polish constitutional court excluded the possibility that the same regulation could serve simultaneously as the object of control and the basis for control proceedings.This results from the essence of constitutional control of the law which in such arrangement of its key elements would simply repeal itself, i.e. would lead to its own invalidation.Subordination of constitutional judges exclusively to the Constitution extends to all actions they perform in serving their office and other consubstantial manifestations of exercising the power to judge.This is a derivative of jurisprudential responsibilities of the Tribunal, which include both passing a final judgment as to compliance of challenged statutes, as well as other acts of application of law.Art. 195 (1) in fine of the Polish Constitution lays down a competence norm for a CT judge to refuse, in specific circumstances, to abide by the CT Act. One of the analytical assumptions is recognition of the finality of CT judgments.The possibility to exclude a provision of the CT Act is an action in the area of application of law.Determination of the legal framework for passing judgments has nothing in common with constitutional control of challenged statutes.Those actions derive from totally different orders and their goals are differe.